Women's participation and their constraints in livestock management activities: A case study of district Bahawalpur in Punjab, Pakistan - Zoia Arshad Awan; Komal Akhtar; Liaqat Ali Khan; Asad Ullah Imran (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Livestock is the most important sector for the economy of Punjab which is performing a vital role in rural livelihoods as a key source of employment for women at the household level. Rural women play a significant role in livestock management activities and this sector is also considered the black gold of Pakistan. The current study was carried out in Bahawalpur, a district of South Punjab, Pakistan to investigate women's participation and constraints in different livestock management. The primary data were collected by using a multistage random sampling technique from the rural women (n=200) through a well-structured questionnaire. Simple descriptive statistics were used to analyze the data. Regarding socioeconomic characteristics majority of the female respondents were middle-aged (44%), married (77%), illiterate (80%) and had almost ~15 years of experience in livestock management. Results revealed that women were owned almost 53% more animals as compared to men, and had possessed animals were mostly cow, calf, goat and sheep. Women's participation in livestock management was found significantly high by 86% (at p≤0.001) than men, where women had shown higher time allocation for various livestock management activities. It was noticed that major constraints faced by women in the Bahawalpur region for livestock management were the high cost of veterinary services for animal treatment, poor access to training and loan facilities. This study will help in the execution of future policies for rural development in the provision of credit and livestock training facilities for women to encourage their participation in livestock production.